1995
DOI: 10.1111/j.1439-0485.1995.tb00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Population Ecology of the Amphipod caprella equilibra Say in a Lagoon Estuary (Northern Adriatic Sea, Italy)

Abstract: Abstract. The population ecology and dynamics of Cuprella equilibra were studied in a lagoon estuary of the Northern Adriatic Sea during 1985 to 1986. The breeding activity showed peaks in April and September and a decrease in summer due both to high temperatures and a dystrophic crisis; breeding stops in winter. Females produced more than one brood per year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…Cockman and Albone (1987) found, after 24 h under laboratory conditions, LC50 values of 7.5 and 11.5 for C. scaura and C. equilibra respectively. A decade before detection of C. scaura in the Lagoon of Venice, Sconfietti and Luparia (1995) found that, although C. equilibra was more abundant in saltier waters at this lagoon, it was able to tolerate partially estuarine conditions (since it tolerated salinity decreases up to 15 psu), being more euryhaline than other common fouling caprellids. Furthermore, C. equilibra has also commonly been found in hypersaline waters (>40 psu), like those present along the Suez Canal (Emara and Belal, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Cockman and Albone (1987) found, after 24 h under laboratory conditions, LC50 values of 7.5 and 11.5 for C. scaura and C. equilibra respectively. A decade before detection of C. scaura in the Lagoon of Venice, Sconfietti and Luparia (1995) found that, although C. equilibra was more abundant in saltier waters at this lagoon, it was able to tolerate partially estuarine conditions (since it tolerated salinity decreases up to 15 psu), being more euryhaline than other common fouling caprellids. Furthermore, C. equilibra has also commonly been found in hypersaline waters (>40 psu), like those present along the Suez Canal (Emara and Belal, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Although the number of studies on the ecological and behavioural aspects of the Caprellidea are increasing ( e.g., density fluctuation and population ecology: Bynum, 1978; Takeuchi et al , 1990; Sconfietti & Luparia, 1995; life‐histories under laboratory conditions: Takeuchi & Hirano, 1991, 1992; clinging behaviour: Takeuchi & Hirano, 1995; Guerra‐García, unpublished data) no work has yet been published on the relation ­between physico‐chemical parameters and the specific community of the Caprellidea.…”
Section: Discussionmentioning
confidence: 99%
“…Caine 28 reported 90% survival after 5 days at 23–25 for Caprella laeviuscula (10°C), Caprella stiriata (5°C) and Metacaprella kennerlyi (10°C) based on regression analysis of final survival percentages. The distributions of C. equilibra and Caprella dilatata inhabiting the estuaries of the Northern Adriatic Sea in Italy indicate that the two species have adapted to an estuarine environment and have reduced tolerance of salinity by 15 29 . Caprella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The distributions of C. equilibra and Caprella dilatata inhabiting the estuaries of the Northern Adriatic Sea in Italy indicate that the two species have adapted to an estuarine environment and have reduced tolerance of salinity by 15‰. 29 Caprella spp. exhibit minimal migration ability, having evolved reduced abdominal appendages which make them well adapted for clinging to substrates such as algae and hydroids, whereas other amphipods use their longer appendages for swimming.…”
Section: Discussionmentioning
confidence: 99%